Distributed crowd-based annotation of soccer games using mobile devices - Barros, B. (2018)
Soccer is one of the most loved sports in the world. Millions of people either follow the sport or are actually involved in its practice. Soccer also moves huge financial amounts every year and therefore teams always thrive to be better than the competition. New technologies have become a common place both in the preparation of the games and on the analysis of the games after they are concluded. In this paper, the authors will present a developed system, based on the usage of distributed mobile devices, that will enable the annotation of soccer matches, either in real time or after the matched is concluded (through the observation of other media). The capture of relevant events in the game can be used to better analyse the game and the performance of individual players fostering improvements and better decisions in the future. The application is implemented in the Android platform so that it can be easily installed by typical soccer fans empowering them as match annotators. This crowd of annotators, although not experts, can collectively provide a robust and rich annotation for soccer matches.